Do financial markets care about SRI? Evidence from mergers and acquisitions - Aktas, Nihat; de Bodt, Eric; Cousin, Jean-Gabriel (Journal of Banking & Finance, 2011)
Mergers and acquisitions offer a framework for shedding new light on the stock market performance of socially responsible investments (SRI). We use Innovest’s Intangible Value Assessment (IVA) ratings as a measure of firms’ ability to cope with social and environmental risks. The IVA ratings allow us to uncover a positive relation between acquirer gains and the level of the target’s social and environmental risk management practices. Our findings suggest that the stock market rewards the acquirer for making socially and environmentally responsible investments. We also document that the environmental and social performance of the acquirer increases following the acquisition of a SRI aware target. These results are consistent with acquirer learning from the target’s SRI practices and experiences.